Lycopene in the Prevention of Radiation-Induced Esophagitis - Coskun, Hatice; Andic, Fundagul; Daglioglu, Yusuf Kenan; Doran, Figen; Şahin, Kazım; Tunali, Candas; Küçük, Ömer (Routledge Journals, Taylor & Francis Ltd, 2017)
We aimed to research whether lycopene (L) could prevent radiation-induced acute esophageal toxicity in Wistar albino rats. 60 rats were placed in five groups as follows: control, L, radiotherapy (RT), L before RT (L + RT), and L before and after RT (L + RT + L). 6mg/kg bw/day L was administered 7days in the L group, 7days before RT in the L + RT group, and 7days before and after in the L + RT + L group. 35Gy thoracic RT was performed. Serum L levels were measured, and the esophagi were evaluated histopathologically for intraepithelial degenerative changes-necrosis, vacuole formation, inflammation, regeneration-mitosis, and subepithelial bulla formation. L levels were significantly higher in the L receiving groups. All histopathologic results were significantly worse in the RT group than in the none-RT groups. The L + RT and the L + RT + L groups had better results than the RT group. Grade 2-3 degenerative changes-necrosis and vacuole formation were significantly lesser in the L + RT and the L + RT + L groups than those in the RT group. There was a trend toward decreased subepithelial bulla formation and inflammation in the L + RT and the L + RT + L groups compared to the RT group. Regeneration-mitosis was insignificantly lesser in the L + RT and significantly fewer in the L + RT + L groups than that in the RT group.
Keywords: Cell Lung-Cancer; 3-Dimensional Conformal Radiotherapy; Irradiation-Induced Esophagitis; Superoxide-Dismutase Transgene; High-Dose Radiation; Group Rtog Trials; Concurrent Chemotherapy; Gene-Therapy; Randomized-Trial; Singlet Oxygen